Persistence of attenuated rev genes in a human immunodeficiency virus type 1-infected asymptomatic individual. - Iversen, A K (1995)
With the goal of examining the functional diversity of human immunodeficiency virus type 1 (HIV-1) env genes within the peripheral blood mononuclear cells of an asymptomatic individual, we substituted four complete env genes into the replication-competent NL4-3 provirus. Despite encoding full-length open reading frames for gp120 and gp41 and the second coding exon of tat and rev, each chimera was replication defective. Site-directed mutagenesis of codon 78 in the Rev activation domain (from a hitherto unique Ile to the subtype B consensus Leu) partially restored infectivity for two of three chimeras tested. Similarly, mutagenesis of rev codon 78 of NL4-3 from Leu to Ile partially attenuated this virus. Ile-78 was found in all 13 clones examined from samples taken from this asymptomatic subject 4.5 years after infection, including 9 from peripheral blood mononuclear cells and 4 from a virus isolate, as well as 4 additional clones each from peripheral blood mononuclear cells sampled 37 and 51 months later. We next examined conservation of the Rev activation domain within and among long-term survivors (LTS) and patients with AIDS, as well as T-cell-line-adapted strains of HIV-1. Putative attenuating mutations were found in a minority of sequences from all five LTS and two of four patients with AIDS. Of the 11 T-cell-line-adapted viruses examined, none had these changes. Among and within LTS virus population had marginally higher levels of diversity in Rev than in Env; patients with AIDS had similar levels of diversity in the two reading frames; and T-cell-line-adapted viruses had higher levels of diversity in Env. These results are consistent with the hypothesis that asymptomatic individuals harbor attenuated variants of HIV-1 which correlate with and contribute to their lack of disease progression.